2018
DOI: 10.1038/s41401-018-0080-0
|View full text |Cite
|
Sign up to set email alerts
|

Low serum osteocalcin levels are correlated with left ventricular systolic dysfunction and cardiac death in Chinese men

Abstract: Osteocalcin is a newly identified type of cytokine secreted by osteoblasts, which has an endocrine function, mediates energy and glycol-lipid metabolism, and is closely related to cardiovascular diseases. In this study, we investigated the value of serum osteocalcin levels in predicting left ventricular systolic dysfunction and cardiac death. A total of 258 patients in the Department of Cardiology were included. Two-dimensional echocardiography was performed in all the subjects. The cardiac death of subjects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
12

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 35 publications
0
6
0
12
Order By: Relevance
“…At the same time, this study through multivariate logistic regression analysis found that NT-pro BNP was a risk factor for MACE and NYHA class in patients, which means that NT-pro BNP is can be the basis for grading and prognosis of patients with DHF. However, there are some studies have shown that men have lower NT-pro BNP levels than women [ 16 ]. Renal dysfunction leads to sodium-water retention, resulting in increased cardiac pressure load, and finally increased left ventricular wall pressure, resulting NT-pro BNP release [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, this study through multivariate logistic regression analysis found that NT-pro BNP was a risk factor for MACE and NYHA class in patients, which means that NT-pro BNP is can be the basis for grading and prognosis of patients with DHF. However, there are some studies have shown that men have lower NT-pro BNP levels than women [ 16 ]. Renal dysfunction leads to sodium-water retention, resulting in increased cardiac pressure load, and finally increased left ventricular wall pressure, resulting NT-pro BNP release [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have documented that the concentration of serum OC was lower among patients as compared to healthy controls [43,46]. In a case-control study, levels of serum OC were lower among patients with fatty liver [46], diabetes [68], and cardiovascular disease [69]. In addition, studies on populations with inflammatory diseases such as rheumatoid arthritis reported a positive association between OC and CRP levels [70].…”
Section: Discussionmentioning
confidence: 99%
“…Данные клинического исследования показали, что уровни остеокальцина в крови коррелируют с функцией сердца. Авторы сообщили о взаимосвязи между уровнем остеокальцина в крови и фракцией выброса левого желудочка, обнаружив, что более низкие уровни остеокальцина в крови коррелировали с более высоким риском систолической дисфункции левого желудочка [18]. Опубликованы результаты, свидетельствующие о том, что кальций (кальциноз) коронарных артерий независимо ассоциирован с уровнем в крови остеокальцина [11].…”
Section: результатыunclassified